Interspecies comparisons of tissue DNA damage, repair, fixation, and replication. - Slaga, T J (1988)
The many anatomical, physiological, and biochemical differences among various mammalian species make it difficult to extrapolate carcinogenic potency data from animals to humans. The process is further complicated by the multistep origin of most malignant tumors in animals and humans due to the interaction of target cells with both endogenous and exogenous factors. Species differences in these aspects of carcinogenesis must also be considered when attempting to evaluate the carcinogenic risks of chemicals to humans. Cancer development in animals involves at least three distinct stages: initiation, promotion, and progression. Intra- and interspecies differences in susceptibility to carcinogenesis may be related to any one or a combination of these stages. Variation in species susceptibility to tumor initiation may result from differences in the abilities of various species to metabolize a potential carcinogen to an ultimate carcinogenic form and/or to detoxify the carcinogen. Most comparative studies among species have only revealed subtle differences in metabolism. DNA adducts from several activated carcinogens have been found to be the same in a number of tissues from various species, including humans. Capacity for DNA repair is apparently a critical factor in the initiation of carcinogenesis in target cells of different species but is less critical among mice that differ in susceptibility to two-stage carcinogenesis of the skin and liver. Susceptibility variations among stocks and strains to such carcinogenesis appear to be related to alterations in tumor promotion. Additional comparative studies are critically needed on all aspects of carcinogenesis to permit effective extrapolation of carcinogenic potency data from animals to humans.